Evaluation of the 'Articulate' widening participation intervention aimed at improving soft skills and HE aspirations of students from traditionally under‐represented backgrounds. Issue 1 (6th April 2023) - Banerjee, Pallavi; True, Charlotte; Hart, Rob; Hodgson, Eleanor; Dingwall, Kristi; Shen, Zhimin
Abstract: The 'Articulate' programme is a high‐intensity five‐day widening participation programme designed to help students develop their communication skills and confidence through a range of activities led by an Articulacy tutor and culminates in students taking an examination for the English Speaking Board (ESB) Level 1 Award in speech on the final day. Additionally, students also develop their understanding of and aspirations towards higher education (HE) through sustained interaction with student ambassadors, who support all sessions throughout the week. Based on the conceptual framework of the theory of change, the intervention primarily addresses the barrier of soft skills, including increasing students' self‐belief, while also addressing some of the barriers of socio‐economic factors to HE participation namely knowledge, understanding and likelihood of applying to HE in future, through increased exposure to HE role models. In this paper we report our findings from the evaluation where we are studying the effectiveness of the programme. Through survey questionnaires data was collected from over 698 students in year 9 and year 10, studying at 42 schools across Cornwall, Devon, and Somerset who took part in the 'Articulate' programme, which was run in collaboration with Next Steps South West (NSSW). Results show the majority of participating students went on to perform well in the ESB exam; furthermore, participants were more likely to have positive attitudes towards HE and considered applying to HE in future. The findings will be of particular interest to practitioners and activity providers. Context and implications Rationale for this study: This paper summarises the mid‐term evaluation of an outreach programme designed for under‐represented groups to build their soft (communication) skills and develop their understanding of higher education (HE)—in terms of applying to university, support available and the possibilities HE can offer. Why the new findings matter: It is possible to achieve medium‐term goals only after a sequence of short‐term goals are completed and built together to form a long‐term pursuit. Evaluating these goals is particularly useful for those delivering them and for the funder. Long‐term plans are what we are working towards, but the value of moderate to mid‐term goals is that they let us check our progress and evaluate whether we are still heading towards our long‐term pursuit and whether our plan, design or choices need to change to reach desired outcomes. Implications: We expect the paper will be of particular interest to funders, regulators, practitioners and activity providers delivering similar programmes and will encourage them to evaluate the programmes they run for effectiveness and accountability. Based on the work done by some research team members, the Office for Students has recently published a report encouraging higher education institutions, outreach and activity providers to consider the standards of evidence and programme evaluation. Our work is one example of a mid‐term review for an ongoing programme with long‐term goals. Such reports are relatively rare, and we expect this evidence‐based practice will set a good example for colleagues involved in similar work.